The Influence of Islamic Attributes of Destination towards Destination Loyalty with Tourist Satisfaction as an Intervening Variable - Melika Naifah Antoni; Vidyarini Dwita (Jurnal Kajian Manajemen dan Wirausaha, 2020)
The purpose of this research are to analyze : (1) the influences of Islamic attributes of Destination on Destination Loyalty, (2) the influences of Islamic attributes of destination on tourist satisfaction, (3) the influences of tourist satisfaction on destination loyalty.The type of this research is causative research. The population on this research is Muslim traveler that already visited Kabupaten Pesisir Selatan. The total sample of this research was 281 people by using online questionnaire. The result of research show that (1) Islamic attributes of destination has significant influences on destination loyalty, (2) Islamic attributes of destination has significant influences on tourist satisfaction (3) Tourist satisfaction has significant influence on destination loyalty.For the future research it is better to explore more about variable that can influence destination loyalty.